PENEGAKAN HUKUM PEMERINTAHAN OLEH KEIMIGRASIAN MENGENAI IZIN TINGGAL (VERGUNNING) DI WILAYAH KERJA KANTOR IMIGRASI KELAS II TPI BENGKALIS TAHUN 2018 - Rahman, Azizul; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Immigration Office Class II TPI Bengkalis is one Immigration Office that stay in Riau Province. In Addition to immigration attendance sector, Immigration Office Class II TPI Bengkalis also carry out 2 (two) instrumental in maintenance of Government Law such us surveillance as preventive way and the maintenance of suction. Immigration Office Class II TPI Bengkalis has did efforts surveillance as a preventive way to appellant of living permit, owner of living permit, living permit that will be finish prevail period also existence and activity of foreign citizen in job district of Immigration Office Class II TPI Bengkalis. We can not deny that Immigration Office Class II TPI Bengkalis also did the maintenance of sunction to the offender immigration such as foreign citizen that overstay, living permit abuse also other immigration infraction. It has exist the data 2018, Immigration Office Class II TPI Bengkalis only one time did punishment action of immigration such as â€œprojustisiaâ€ and deportation to foreign citizen who finish prevail period. The method that used in this research is descriptive method with qualitative research. Kind of research data are primary data and secondary data. The technique of collecting the data in this research is documentation and interview. The analysis technique of the data that used is data analysis qualitative descriptive.The result of this research is Immigration Office Class II TPI Bengkalis has did the maintenance of sunction for those did immigration infraction, but only in sub district Bengkalis region. This case caused in 2018 come out decision of Law Cabinet Minister and HAM RI related the change of job district of immigration office, previously Immigration Office Class II TPI Bengkalis only have 4 (four) sub district as job district, and for now become 11 (eleven) sub district or consist of 3 (three) island that have a difference as job district. The Blocked factor such as, deficiency of human resources for placed employee or special employee to surveillance in Duri district and Rupat, so rated lack of optimum in surveillance and calculation also distance that traveled to do surveillance, quick response to the scene when there is any information of infraction immigration.Â Â Keywords: The Maintenance Of Government Law, Living Permit, Matter Pertaining To Immigration